1994
DOI: 10.1111/j.1432-1033.1994.tb19047.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNA encoding neurotrophins and neurotrophin receptors in rat thymus, spleen tissue and immunocompetent cells

Abstract: The expression of neurotrophin and neurotrophin receptor mRNAs was examined using RNase protection assays and Northern‐blot analysis in rat thymus, spleen tissue and immunocompetent mononuclear cells purified from these two organs. Nerve growth factor, brain‐derived neurotrophic factor, neurotrophin‐3 and neurotrophin‐4 mRNAs were all expressed in thymus and spleen tissue although at different levels, while immunocompetent cells expressed neurotrophin‐3 and neurotrophin‐4 mRNAs. Thymus and spleen tissue expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 64 publications
(37 reference statements)
4
70
1
6
Order By: Relevance
“…This hypothesis is supported by in vivo studies showing NGF-r expression on stromal and immune cells within lymphoid organs (96)(97)(98)(99).…”
Section: Ngf and The Immune Systemsupporting
confidence: 64%
“…This hypothesis is supported by in vivo studies showing NGF-r expression on stromal and immune cells within lymphoid organs (96)(97)(98)(99).…”
Section: Ngf and The Immune Systemsupporting
confidence: 64%
“…Serial coronal cryostat sections (14 m) were processed for hybridization with radioactive riboprobes (Ibanez et al, 1992;Laurenzi et al, 1994;Lindefors et al, 1995) as described previously (Canals et al, 2001). Antisense cRNA probe to detect the transcripts of neurotrophins was prepared by in vitro transcription using T3 or T7 RNA polymerase (Promega) and […”
Section: Methodsmentioning
confidence: 99%
“…All neurotrophins have been detected in the rat spleen at the mRNA level (Maisonpierre et al, 1990;Timmusk et al, 1993;Laurenzi et al, 1994), while NT-3 has also been detected at the protein level (Katoh-Semba et al, 1996). Thus, neurotrophins of local or systemic origin (especially NGF (Carlson et al, 1998), whose levels are altered during certain infectious states (Ahmed et al, 1998)) could act on DC through p75 NTR and be among the soluble factors controlling DC maturation (Caux et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The human (Yamamoto et al, 1996) and rat (Ernfors et al, 1988;Laurenzi et al, 1994;Lomen-Hoerth and Shooter, 1995) spleen contain mRNA for p75 NTR . In immunohistochemical studies, the p75 NTR -expressing cell types have been identified as either B-lymphocytes (Chesa et al, 1988) or follicular dendritic cells (Labouyrie et al, 1997;Fanburg-Smith and Miettinen, 2001) of the human spleen.…”
mentioning
confidence: 99%